2016
DOI: 10.1038/s41598-016-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pneumonia and lung cancer on mortality of women with hypertension

Abstract: Essential hypertension is one of the most severe women's health problems. Modern life brings more chances of pulmonary diseases to human. The purpose of the study is to investigate weather pneumonia and lung cancer are associated with the mortality of women with hypertension in different age. A crosssectional retrospective study was conducted in women with hypertension, who were admitted into our hospital in 2004-2013. 14219 women were enrolled and 68.8 ± 12.2 year old (y). Isolated hypertension was 14.7%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…It is estimated that by 2035 the number of lung cancer deaths will increase globally by 86%. 1 Lung cancer increasingly has become recognized as a systemic disorder associated with diabetes mellitus, obesity, and hypertension, [2][3][4] which are known risk factors for cardiovascular disease. It has been hypothesized that lung cancer is associated with increased cardiovascular risk, especially the risk for coronary heart disease and stroke.…”
Section: Lung Cancer and Risk Of Cardiovascular Disease: A Meta-analymentioning
confidence: 99%
“…It is estimated that by 2035 the number of lung cancer deaths will increase globally by 86%. 1 Lung cancer increasingly has become recognized as a systemic disorder associated with diabetes mellitus, obesity, and hypertension, [2][3][4] which are known risk factors for cardiovascular disease. It has been hypothesized that lung cancer is associated with increased cardiovascular risk, especially the risk for coronary heart disease and stroke.…”
Section: Lung Cancer and Risk Of Cardiovascular Disease: A Meta-analymentioning
confidence: 99%
“… 25 A pre-treatment CT radiomic feature ( Law’s Energy ) in a cohort of 47 patients with early-stage non-small cell lung cancer (NSCLC) was significantly predictive for EGFR-mutation status. 8 Interestingly, this study also showed that the difference in one radiomic feature ( Gabor Energy ) between baseline and an on-treatment CT (3 weeks after beginning the anti-EGFR gefitinib) was associated with mutation status. Tumour volume and maximum diameter were the two other significant predictive parameters, but these only weakly correlated with this radiomic feature.…”
Section: Radiomics For Cancer Diagnosismentioning
confidence: 55%
“…Activity related to hand orientation was found in F2 29 and in V6A 30 , both areas part of the reach-related dorso-medial stream, while reach activity was found in F5 31 , an area part of the grasp-related dorso-ventral stream. Other studies added support for these findings 32 36 , warranting further investigation into the separation between reaching and grasping processes in the brain.…”
Section: Introductionmentioning
confidence: 80%
“…In parietal cortex, most of area V6A was exclusively connected to the dorso-medial network and only small parts were functionally connected with both networks. Area V6A has been extensively investigated with respect to its anatomical connectivity 7 , 13 , 62 and electrophysiological selectivity for reaching as well as grasping behavior 23 , 33 , 34 , 36 , 63 . However, the presence of selective neural activity does not imply a causal influence, as outlined in the introduction.…”
Section: Discussionmentioning
confidence: 99%